Molecular detection of Coxiella burnetii in raw milk of cattle in Karbala province - Muhye, Nawras Amer; Kadhim , Kadhim S.; Salih, Mohammed Asad (Journal of Kerbala for Agricultural Sciences, 2024)
Coxiella burnetii causes Q fever in humans and coxiellosis in animals. It was widely distributed worldwide; the main reservoirs are sheep, goats, and cattle. This study has been conducting to detection C. burnetii in raw milk of cattle (50) milk samples were randomly collected from dairy cattle from different areas of major districts of Karbala Province in interval during the period from November 2023 to April 2024 under aseptic conditions, using polymerase chain reaction (PCR) showed that C. burnetii IS1111 gene abundance was 14% in seropositive animals. This study presents the initial molecular identification of C. burnetii in the province of Karbala, indicating its prevalence among cattle. Furthermore, individuals who consume Unpasteurized milk and/or products may have a heightened susceptibility to infection.